Plasma kisspeptin levels in lactational amenorrhea. (3rd October 2017) - Kotani, Masato; Katagiri, Fumihiko; Hirai, Tsuyoshi; Kagawa, Jiro; Tanaka, Issei
Abstract: The kisspeptin is a neuropeptide to play physiological roles in regulating gonadotropin-releasing hormone secretion in the hypothalamus. In human plasma, the kisspeptin concentration is measured, but gonadotropin-releasing hormone is not. This study aims to understand the physiological roles of the circulating kisspeptin in lactational amenorrhea in humans because prolactin reduces the kisspeptin expression and luteinizing hormone secretion resulting in anovulations in rodent brains. Plasma kisspeptin levels were measured in 11 subjects in lactational amenorrhea and in four cases with pathological amenorrhea by different etiologies for comparison using the enzyme immunoassay specific for human kisspeptin. The plasma kisspeptin levels in the 11 women with lactational amenorrhea were 15.2 ± 2.5 fmol/mL (mean ± SD) which were not significantly different as compared with 16.5 ± 4.8 fmol/mL (mean ± SD) in four age-matched women with menstrual cycles as we reported previously. In the four cases with pathological amenorrhea, their plasma kisspeptin levels were from 5.8 to 13.7 fmol/mL. This study demonstrated that the plasma kisspeptin levels were not totally reduced in lactational or pathological amenorrhea. These results suggest the physiological roles of the circulating kisspeptin are different from the role in the brain.